The effect of change-in-control covenants on takeovers: Evidence from leveraged buyouts - Billett, Matthew T.; Jiang, Zhan; Lie, Erik (Journal of Corporate Finance, 2010)
Change-in-control covenants first became commonplace towards the end of the takeover wave in the 1980s. We examine merger and acquisition activity from 1991 to 2006 to see how such covenant protection influences the wealth effects and probability of takeovers. Examining a sample of leveraged buyouts (LBOs) we find bondholders with such covenant protection experience average wealth effects of 2.30% while unprotected bonds experience −6.76% upon the announcement of an LBO. Furthermore, we document that the existence of bondholder change-in-control covenants cuts the firm's probability of being targeted in an LBO in half. We also find that change-in-control covenants reduce the probability of being targeted in non-LBO takeovers, but the effect appears less dramatic.